EFFECTS OF NATURAL AND URBAN SOUNDSCAPES ON AFFECTIVE STATES AND CONCENTRATION IN EDUCATIONAL SETTINGS - Rusdi, Ahmad; Nurtjahjo, Fani Eka; Sari, Mutiara; Musliha, Elmira Syamsa; Nadhira, Hasya; Maharani, Rahmanisa; Maarisca, Gladys; Azzah, Aisyah Raihana (UI Scholars Hub, 2026)
Although environmental noise has been extensively studied, limited research has compared the differential effects of natural and urban soundscapes on psychological outcomes. This pilot study examined the impact of urban and natural soundscapes on students’ concentration and affective responses. A pre–post experimental design with two groups was implemented, involving 12 undergraduate participants (aged 18–24 years) with equal gender representation. Concentration was measured using the polyshape board, which was preliminary validated in this study, while affective states (pleasantness and arousal) were assessed using the Affect Grid Scale (AGS) before and after exposure. Given the limited sample size and the ordinal data, the Wilcoxon Signed-Rank test was applied. The analysis revealed a significant difference in concentration between the two conditions (p=0.037), with higher and more stable scores observed under natural sound exposure (M=32.9; Md=35.5) compared to urban sound conditions (M=31.1; Md=34.5). Manipulation checks indicated no significant difference in pleasantness (p=0.224), while arousal differed significanly between conditions (p=0.045), with higher arousal reported in the urban sound conditions. These findings suggest that natural sounds may be associated with improved concentration and reduced arousal in controlled educational and laboratory settings. However, given the small sample size and short exposure duration, the findings should be considered preliminary and require further investigation with higher and more diverse samples.